A dynamic model for supercritical once-through circulating fluidized bed boiler-turbine units. (15th February 2022) - Zhang, Hongfu; Gao, Mingming; Fan, Haohao; Zhang, Kaiping; Zhang, Jiahui
Abstract: It is urgent to establish a dynamic model of once-through supercritical circulating fluidized bed (SCFB) power generation units in order to explore the flexible operation mode. This study aims to establish such a dynamic model with the balance between model complexity and accuracy. Within the analysis on operation characteristics of SCFB units, some reasonable assumptions and simplifications were introduced. Then, a dynamic model structure was derived from mass, energy balance laws as well as thermodynamic principles. And the unknown parameters in the model were identified by regression analysis and quantum genetic algorithm, combined with running data from a 350 MW SCFB unit. After this, the open-loop step responses and closed-loop experiments were developed to further validate the established model. The simulation results show that all model outputs can track the dynamic trends of running data in different load conditions with the satisfactory accuracy. More importantly, the model captures the special dynamic characteristics of the SCFB unit. Therefore, the model can be feasible and applicable for advanced control algorithms test and flexible operation control system design of SCFB units. Highlights: Operation characteristics of SCFB units are considered in the model establishment. A dynamic model of a 350 MW supercritical circulating fluidized bed unit is developed. The open-loop and closed-loop experiments are conducted to validate the model. The analysis on dynamic characteristics of SCFB units is presented.